Cognitive Reasoning and Style: Do Differences of Cognitive Style Result Differences in Reasoning Ability? - Nurdin Nurdin (Universitas Muhammadiyah Enrekang, 2022)
The study is a qualitative research. The study aims at describing the differences of reasoning ability of students in solving linear program problems based on cognitive styles between FI and FD in class X at SMK Baramuli Pinrang. Subjects of the study were taken by employing test GEFT. Data were collected through written test of problem solving ond interview. Data were obtained through the result of written test and interview which were analyzed using Miles and Huberman model. The results of the study indicate that the differences of reasoning ability of students in solving problem based on cognitive styles between FI and FD in each of reasoning math indicator indicate that FI students can do reasoning and math communication better than FD students.